2017
DOI: 10.1007/s40203-017-0037-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of protein–ligand solvation and desolvation on transition state thermodynamic properties of adenosine A2A ligand binding kinetics

Abstract: Ligand-protein binding kinetic rates are growing in importance as parameters to consider in drug discovery and lead optimization. In this study we analysed using surface plasmon resonance (SPR) the transition state (TS) properties of a set of six adenosine A receptor inhibitors, belonging to both the xanthine and the triazolo-triazine scaffolds. SPR highlighted interesting differences among the ligands in the enthalpic and entropic components of the TS energy barriers for the binding and unbinding events. To b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 81 publications
1
14
0
Order By: Relevance
“…Interestingly, A 2A AR bears Ala265 instead of Lys265 on the ECL3, while Lys168 and Lys173 (ECL2) are farther from the binding site, compared to A 1 AR. This is consistent with mutagenesis studies that demonstrated the importance of these lysine residues forthe binding of several A 1 AR ligands [39][40][41]. On A 2A AR, Z48 reachedthe orthosteric site producing the classic interactions fingerprint of the ARs antagonists.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, A 2A AR bears Ala265 instead of Lys265 on the ECL3, while Lys168 and Lys173 (ECL2) are farther from the binding site, compared to A 1 AR. This is consistent with mutagenesis studies that demonstrated the importance of these lysine residues forthe binding of several A 1 AR ligands [39][40][41]. On A 2A AR, Z48 reachedthe orthosteric site producing the classic interactions fingerprint of the ARs antagonists.…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that the ligand binds A 1 AR and A 2A AR with the same conformation, but differently interacting with water molecules nearby ECL3. From this standpoint, and in analogy with [41], we propose these "happy" water molecules contribute to the ligand stabilization in A 1 AR ( Figure S16), but not in A 2 AR ( Figure S17). An alternative and unique LC4 binding mechanism was sampled only on A 1 AR, with a metastable state before the final complex formation.…”
Section: Discussionmentioning
confidence: 72%
“…The (un)binding kinetics have a major impact on both pharmacodynamics [55][56][57] [60][61][62][63] and small changes in either the structure of the ligand or the protein can alter the nature and the position of the transition states along the (un)binding routes 64 .…”
Section: Towards the Definition Of The Structure-binding/unbinding Pamentioning
confidence: 99%
“…A method combining SuMD, metadynamics, and suMetaD, enables the investigation of ligand binding and dissociation and retrieval of the transition state conformations of the two processes [146]. This algorithm was applied to A 2A AR and six ligands, three xanthines (XAC, DPCPX, KW3902), and three triazolotriazines (ZMA, Z48, Z80), whose transition state thermodynamics appeared to be connected to the characteristics of water molecules solvating the binding pocket and the compounds.…”
Section: Water Contribution In Ligand-bindingmentioning
confidence: 99%